2022
DOI: 10.1111/tpj.15717
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive evolution of Euryale ferox to the aquatic environment through paleo‐hexaploidization

Abstract: Occupation of living space is one of the main driving forces of adaptive evolution, especially for aquatic plants whose leaves float on the water surface and thus have limited living space. Euryale ferox, from the angiosperm basal family Nymphaeaceae, develops large, rapidly expanding leaves to compete for space on the water surface. Microscopic observation found that the cell proliferation of leaves is almost completed underwater, while the cell expansion occurs rapidly after they grow above water. To explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 132 publications
0
17
0
Order By: Relevance
“…The filtered sequenced sequence was compared with the reference genome E. ferox . Trinity software was used for a series of sequence assembly of high-quality sequencing data, and long and high-quality transcripts were obtained for subsequent research and analysis [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The filtered sequenced sequence was compared with the reference genome E. ferox . Trinity software was used for a series of sequence assembly of high-quality sequencing data, and long and high-quality transcripts were obtained for subsequent research and analysis [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…AKE, ancestral karyotype of E. ferox . Figure adapted from Wu et al., 2022. [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Figurementioning
confidence: 99%
“…Analysis of these genome sequences showed that E. ferox has undergone an ancient allo-hexaploidization event that N. colorata has not. In this issue, Peng Wu and colleagues investigated this genome triplication and tried to understand how it contributed to the development of leaves in E. ferox (Wu et al, 2022). Most water lilies, including N. colorata, develop relatively small leaves; however, E. ferox develops gigantic prickly floating leaves that can grow up to 2 m in diameter, much like the leaves of the Santa Cruz waterlily (Victoria cruziana), a popular water plant in botanical gardens.…”
mentioning
confidence: 99%
“…Euryale ferox, belonging to the Nymphaeaceae and genus Euryale, is a characteristic aquatic vegetable and has become recognized as a health food (Wu et al, 2022b). It has the effect of tonifying kidney, tonifying spleen (Song et al, 2011;Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%